Effect of Government Revenues and Gross Regional Bruto to Reduce Poor - Susanti, Susi; Paramita, Ahsani (Phinisi Applied Accounting Journal, 2024)
The aim of the research is to determine the effect of government spending on the education sector, life expectancy and per capita income on poverty through government income in South Sulawesi Province. Data was obtained from the South Sulawesi Central Statistics Agency for the period 2008-2022. This research uses quantitative research with the Path Analysis method. The results show that directly the variables of government expenditure in the education sector and per capita income have an effect on PAD, life expectancy has no effect on PAD. Then, the government expenditure variable in the education sector, life expectancy has no effect on poverty, while per capita income has a significant effect on poverty. Indirectly, the variables of government expenditure in the education sector and UHH on poverty through PAD are more dominant in reducing poverty rates, while the total influence of the per capita income variable on poverty through PAD is lower than the indirect effect through PAD in South Sulawesi Province.